The influence of big five personality traits on irrational beliefs among primary school teachers in Muar, Johor - Chua, Yong Sheng (2017)
The purpose of this study is to identify the influence of the Big Five personality traits on irrational beliefs among primary school teachers in Muar, Johor. The research objectives of this study are to identify the personality traits of primary school teachers based on Big Five Model and the level of irrational beliefs among primary school teachers and to identify the Big Five personality traits that contribute most to the irrational beliefs among primary school teachers. 140 primary school teachers from sixteen primary schools in Muar, Johor were selected as the respondents for this study. The instruments employed for the data collection were Big Five Inventory (BFI) and Questionnaire of Teachers Irrational Beliefs - Revised (QTIB-R). The analysis of the data was conducted using the Statistical Package for Social Sciences (SPSS) version 19. The analyses comprised of normality test and multiple regression. The findings revealed that the primary school teachers possess a moderate level of Openness to Experience, Conscientiousness, Extraversion, Agreeableness and Neuroticism, while the level of irrational beliefs among primary school teachers also moderate. Meanwhile, there are significant influences of the Neuroticism (β = .353, p < .05), Openness to Experience (β = .217, p < .05), and Extraversion (β = .276, p < .05) traits on irrational beliefs among primary school teachers. Among the three personality traits, Neuroticism makes the best contribution, which is 10.5 % of the variance in explaining the irrational beliefs. Meanwhile, there are no significant influences of the Conscientiousness (β = .012, p > .05) and Agreeableness (β = .032, p > .05) traits on irrational beliefs among primary school teachers in Muar, Johor. In conclusion, this study was able to identify the personality traits and irrational beliefs among primary school teachers and identify the influence of the Big Five personality traits on irrational beliefs among primary school teachers.